2010
DOI: 10.1111/j.1582-4934.2010.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine-mediated gene delivery into human bone marrow mesenchymal stem cells from patients

Abstract: Transplantation of mesenchymal stem cells (MSCs) derived from adult bone marrow has been proposed as a potential therapeutic approach for post-infarction left ventricular (LV) dysfunction. However, age-related functional decline of stem cells has restricted their clinical benefits after transplantation into the infarcted myocardium. The limitations imposed on patient cells could be addressed by genetic modification of stem cells. This study was designed to improve our understanding of genetic modification of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 42 publications
5
56
2
1
Order By: Relevance
“…In the evaluation of chemical-mediated transfection, we found that PEI provided a significant level of transfection efficiency in fMSCs. Our results are in accordance with a study by Wang et al [17] , which showed that genetic modification of human MSCs by PEI with a relatively low efficiency of 4% achieved biologically significant effects in vivo, with transfection efficiency proportional to cells in S phase [17] . Our analysis further supported the use of PEI as a transfection reagent in MSCs over other reagents.…”
Section: Discussionsupporting
confidence: 82%
“…In the evaluation of chemical-mediated transfection, we found that PEI provided a significant level of transfection efficiency in fMSCs. Our results are in accordance with a study by Wang et al [17] , which showed that genetic modification of human MSCs by PEI with a relatively low efficiency of 4% achieved biologically significant effects in vivo, with transfection efficiency proportional to cells in S phase [17] . Our analysis further supported the use of PEI as a transfection reagent in MSCs over other reagents.…”
Section: Discussionsupporting
confidence: 82%
“…Several groups (13,15,21) have previously demonstrated the high transfection efficiency of PEI in various cell types and cell lines. Although PEI has been reported as an efficient transfection tool in human adipose derived stem cells (25), human bone marrow MSCs [50] and a bone marrow derived stem cell line (27), collectively very little work has been reported using PEI as an efficient MSC transfection agent, despite its widespread availability as a vector. The majority of research conducted using gene delivery technology is carried out using readily available cells lines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their several advantages, the low survival rate of MSCs following cell therapy is a major challenge that limits their efficacy in clinical settings (Wang et al 2010). Oxidative stresses and pro-apoptotic factors are well-known causes of MSCs death (Zhu et al 2006).…”
Section: Discussionmentioning
confidence: 99%